2016
DOI: 10.1063/1.4962432
|View full text |Cite
|
Sign up to set email alerts
|

Complex quantum transport in a modulation doped strained Ge quantum well heterostructure with a high mobility 2D hole gas

Abstract: Maksym. (2016) Complex quantum transport in a modulation doped strained Ge quantum well heterostructure with a high mobility 2D hole gas. Applied Physics Letters, 109 (10). 102103. Permanent WRAP URL:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
1
12
2
Order By: Relevance
“…At p = 7.7 × 10 10 cm −2 , ν = 6 at B ∼ 0.53 T is barely resolvable, while ν = 5, 7, and 9 can still be clearly distinguished. This behavior is quite different from what is observed in other Ge 2D hole systems, typically with a much higher hole density [10,19].…”
contrasting
confidence: 91%
“…At p = 7.7 × 10 10 cm −2 , ν = 6 at B ∼ 0.53 T is barely resolvable, while ν = 5, 7, and 9 can still be clearly distinguished. This behavior is quite different from what is observed in other Ge 2D hole systems, typically with a much higher hole density [10,19].…”
contrasting
confidence: 91%
“…It is already shown that in p-Si-Ge the device mobility is reduced significantly below that expected for remote ionized impurity-dominated scattering [35][36][37]. However, in strained p-Ge mobilities of approximately 10 6 cm 2 /Vs are possible [38,39] with the same modulation doping and doping offset distance of 20 nm. This reduction in mobility in p-Ge-Sn devices by approximately 10 3 compared to p-Ge and thermal activation is a consequence of the Sn-vacancy hole trap in the Ge cap layer.…”
Section: A Conductance and Mobilitymentioning
confidence: 95%
“…Those based on p-type SiGe heterostructures are readily compatible with silicon technology, 24 and, thanks to their intrinsically strong spin-orbit coupling, they are an attractive candidate for the development of topological superconducting systems. 22,[25][26][27][28][29][30][31][32] In this work, we present proof-of-concept S-Sm devices in which the semiconducting element consists of an undoped SiGe heterostucture embedding a strained Ge quantum-well (QW). A high-mobility two-dimensional hole gas (2DHG) is electrostatically accumulated in the QW by means of a surface gate electrode.…”
mentioning
confidence: 99%